(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
The purpose of this study is to determine the degree of efficiency in the production of three main agricultural crops – wheat, corn, and sunflower – through an analysis of income, expenses, and profit. The analysis was conducted based on data from a sole proprietor – a farmer who owns, leases, and rents land. The production activity carried out by him in the 2022–2023 business year is efficient due to lower levels of production costs for obtaining finished products. However, in 2023–2024, the technological cost of wheat production is twice as high, leading to reduced profit.